Religious Factors Contributing to Underutilization of Family Planning Methods among Muslim Community in Nepal (SNPRC Journal, 2025)
This paper will analyze the family planning practices in the Muslim community in Nepal. It aims to find the ways in which religious tenets shape the practices of family planning among Muslims in Nepal, as well as the influence of community influencers in this regard. For the purpose of this paper, the researcher has adopted the qualitative approach as well as the exploratory research design. It is a fact that religious beliefs, social structures, and/or customs and traditions have a dominant impact on women’s reproductive health. Almost all of the data for this research was obtained from previous research and studies. The researcher expresses in this paper a paradox. In spite of the enhancements to the availability of family planning services, a number of Muslim women have a dearth of information and/or religious and cultural beliefs which, coupled with the aforementioned factors, contribute to the lack of use of contraceptives. Furthermore, community leaders and religious leaders from the community shape and influence family planning, and, in turn, contribute to the misconceptions that the use of contraceptives is un-Islamic.